Conocimientos de adolescentes embarazadas sobre cuidados básicos del recién nacido en Áreas de salud Nª 1 y 3 de Loja - Potosí Pulache, Karen Madelayne (2013)
The Studio is analytical, qualitative-quantitative, type of cross-section in a group of 60 adolescent pregnant women attending the outpatient Areas of health n ° 1 and 3, Loja's city, during the period from June to November of the 2013. El objective was: to determine the knowledge of adolescent pregnant on the care basic newborn in relation to food, hygiene, temperature controllers, protection and the warning signs; as well as the socio-demographic characteristics of patients and to design an educational proposal. The evaluation was carried out through the application of an interview; obtaining the following results: 93% are age of 15-19 years, 53% are single, 67% are students, 68% is located in the secondary, 60% of the patients has a high level in relation to feeding (breast milk), 65% have higher average in relation to hygiene, 65% has a low level in relation to the thermoregulation55% have a level means in relation to the protection, 58% have a high level in relation to the warning signs in the newborn. In conclusion, the majority of pregnant adolescents is dominated the average level of knowledge, this indicates that they are not adequately prepared to assume the responsibility of caring for and raising to a newborn, since not culminated in a natural way a fundamental stage in his life, stage in which the fundamental processes of the human being are definedwhich therefore makes them unstable, insecure of themselves people. By what this educational manual will serve to promote social participation of adolescents regarding the basic care of the newborn. Key Words: teenage pregnancy, basic care, newborn.